Analysing the effects of access to tractor service on technical efficiency of small-scale farmers in the Mpumalanga Province : a case of the Masibuyele Emasimini Programme - Sechube, Mmakhashu Patience (My University, 2021)
Small-scale farmers are the drivers of many countries in Africa and play an important role in livelihood creation among the poor in rural areas (DAFF, 2012). The efficient use of scarce resources in promoting agricultural production has encouraged a considerable amount of research in determining efficiency differentials of small-scale farmers (Chiona, 2011); especially those engaged in maize as a staple commodity in many parts of the world. The study examined the effect of access to tractor service on technical efficiency of small-scale maize farmers following the implementation of the Masibuyele Emasimini programme in the Mpumalanga province. The objectives of the study were to: (i) Compare and identify the socio-economic characteristics of small-scale maize farmers in the three selected districts of the study, (ii) analyse the socio-economic factors influencing small-scale maize farmers’ access to tractor service, and to (iii) measure technical efficiency of farmers who have access to tractor service. The data collection was carried out in three districts of the Mpumalanga province, that is, Ehlanzeni, Nkangala and Gert Sibande. Farmers producing maize were purposively selected for the study because maize is the most staple food produced in the province, especially on a small-scale level. To effectively cover the study area, a simple random technique was used for sampling with a semi-structured questionnaire administered to 101 farmers. The three districts are heterogeneous in technical aspects, and were therefore treated separately in terms of data collection, analysis and report of findings. The data were further analysed using descriptive statistics, the logistic regression and Cobb-Douglas production function model to address objective one, two and three mentioned above, respectively. The results of the logistic regression model indicated that out of the 9 (Nine) socio-economic variables included in the analysis, 6 (Six) of them (Farmer’s association, irrigation, farmer’s level of education, gender, ownership of land and household size) were found to be significant and influencing access to v tractor service by small-scale maize farmers. Technical efficiency levels revealed that farmers with access to tractor service were more technically efficient than those without access in all districts of the Mpumalanga province. For example, the average technical efficiency for small-scale farmers with access to tractor service in the Ehlanzeni district was 0.68; about 41% higher than those without access with an average technical efficiency of about 0.27. The Cobb-Douglas results on the other hand, revealed that farmers in the Mpumalanga province are experiencing technical inefficiency in maize production due to decreasing returns to scale. Access to tractor service was also negatively insignificant towards maize production in both the Ehlanzeni and Nkangala district, and was found to have a positive but insignificant effect in Gert Sibande. Policy implications are that to improve the efficiency of tractor service (rendered by the Masibuyele Emasimini programme) towards maize production; government should focus on significant factors influencing the access of the following by small-scale maize farmers and the factors are machinery, irrigation, gender, and ownership of land, farmer’s level of education, farmer’s association, and household and land size per district.
Thesis (M. Sc. Agriculture (Agricultural Economics)) -- University of Limpopo, 2021
Keywords: Small-scale farmers; Maize; Tractor service; Farm tractors; Tractors; Farms, Small -- South Africa -- Mpumalanga